ACCESSING SOCIAL THEORY THROUGH CIVILIZATION. - Mickunas, Algis (Problems / Problemos, 2012)
The scientific modern Western pronouncement that everything has to be treated with objective impartiality requires the positing of our own culture as one among others, having no value claim to be privileged in its various pronouncements. The claim to scientific objectivity is an aspect of Western modern culture and belongs only to its interpretive context. Hence, the very claim to Western scientific superiority as having methods to access all phenomena objectively is a culture bound position that cannot be universal. After all, "objectively speaking" other cultures, as equal, have very different understandings that do not include such tandems as "objectivity" or for that matter "subjectivity." Culturally objectively speaking, we cannot deny them their different reading of cultural, and indeed all other, phenomena. To say that the others are wrong would be tantamount to saying that we have a criterion of the "right culture" which belongs only to our culture. But in this sense, one abolishes the treatment of other cultures as given objectively and equivalently. We then would posit our scientific culture as universal and require that all others interpret themselves in terms of our own requirements. If social theory is part of modern western culture, then it is limited by that culture and cannot claim universality.